2005
DOI: 10.1126/science.1115964
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Coordination of Spindle Assembly by Chromosome-Mediated Signaling Gradients

Abstract: During cell division, chromosomes are distributed to daughter cells by the mitotic spindle. This system requires spatial cues to reproducibly self-organize. We report that such cues are provided by chromosome-mediated interaction gradients between the small guanosine triphosphatase (GTPase) Ran and importin-beta. This produces activity gradients that determine the spatial distribution of microtubule nucleation and stabilization around chromosomes and that are essential for the self-organization of microtubules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
281
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(303 citation statements)
references
References 24 publications
13
281
0
9
Order By: Relevance
“…2a, inset). Below this concentration threshold, nucleation events were almost non-existent, in agreement with results obtained previously 27 . Next, using Ran-NPs, we found that the complexes triggered microtubule nucleation and aster selforganization with a morphology and a timescale similar to those when assembled with uncoupled Ran (Fig.…”
Section: Magnetic Nanoparticles Controlling Microtubule Assemblysupporting
confidence: 92%
See 2 more Smart Citations
“…2a, inset). Below this concentration threshold, nucleation events were almost non-existent, in agreement with results obtained previously 27 . Next, using Ran-NPs, we found that the complexes triggered microtubule nucleation and aster selforganization with a morphology and a timescale similar to those when assembled with uncoupled Ran (Fig.…”
Section: Magnetic Nanoparticles Controlling Microtubule Assemblysupporting
confidence: 92%
“…Remarkable studies have enabled the discovery of intracellular gradients of RanGTP, stimulated by RCC1 and emanating from chromosomes, which can be described as a reaction-diffusion process that supports the spindle machinery in cell division 27,29,[35][36][37] . Interestingly, by manipulating RanQ69L-GTP and RCC1 signalling grafted to magnetic nanoparticles, we have demonstrated experimentally how cascading reaction-diffusion signals may directly influence the position of asymmetric microtubule arrays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of imaging techniques allowed direct experimental observation of activity gradients in the control of the mitotic spindle [6,8]. This process involves the diffusible small GTPase Ran.…”
Section: Spatial Gradients In Single-protein Modules Activity Gradienmentioning
confidence: 99%
“…For instance, fluorescence resonance energy transfer-based biosensors enabled the detection of gradients of the small GTPases Cdc42 [5] and Ran [6][7][8] as well as of phosphorylated stathmin, a microtubule-binding protein [9]. With suitable probes, even highly unstable enzyme-substrate complexes can nowadays be monitored with sub-cellular spatial resolution [10].…”
Section: Introductionmentioning
confidence: 99%